Hubungan Dukungan Orang Tua dan Disiplin Belajar dengan Hasil Belajar Geografi Siswa Kelas X SMA Negeri 1 Kuta Cot Glie - Nurjannah, Nur Jannah (Sosio-Didaktika: Social Science Education Journal, 2023)
High learning outcomes are the hope of all students, parents, schools and the government. The school's hope is that 100% of students can meet the Minimum Completeness Criteria (KKM) that the teacher has set. However, the reality that occurred was not as expected. Based on the results of observations at SMAN 1 Kuta Cot Glie, there are still very many students who have not met the KKM. In addition, a phenomenon that often occurs in schools today is the large number of students who do not comply with the rules and lack of discipline at school. The formulation of the problem in this research is whether there is a relationship between parental support and learning discipline with the Geography learning outcomes of class X students at SMA Negeri 1 Kuta. Cot Glie. This research aims to determine the relationship between parental support and learning discipline with the Geography learning outcomes of class X students at SMA Negeri 1 Kuta Cot Glie. This research uses a quantitative approach with a correlation research type. The population in this study was all Class X IPS students at SMAN 1 Kuta Cot Glie totaling 42 students using a total sampling technique. Data collection techniques are documentation and questionnaire techniques. Data analysis was carried out by calculating multiple correlations and significance tests. The correlation calculation result is 0.33, including a low category correlation with a coefficient of determination of 11.05%. The significance calculation value obtained is Fcount (2.42) < Ftable (3.25) so that Ha is rejected. Therefore, it can be concluded that there is no significant relationship between parental support and learning discipline with the Geography learning outcomes of class X students at SMA Negeri 1 Kuta Cot Glie.Keywords: Relationship, Parental Support, Learning Discipline, Learning Results